Gut microbiota-mitochondrial crosstalk in obesity: novel mechanistic insights and therapeutic strategies with traditional Chinese medicine - Wen, Lingmiao; Yang, Kun; Wang, Jiexin; Zhou, Hang; Ding, Weijun (Frontiers in Pharmacology, 2025)
Obesity rates are rising globally and have become a major public health issue. Recent research emphasizes the bidirectional communication between gut microbiota and mitochondrial function in obesity development. Gut microbiota regulates energy metabolism through metabolites that impact mitochondrial processes, such as oxidative phosphorylation, biogenesis, and autophagy. In turn, alterations in mitochondrial function impact microbiota homeostasis. Traditional Chinese medicine (TCM), which encompasses TCM formulas and the metabolites of botanical drugs, employs a holistic and integrative approach that shows promise in regulating gut microbiota–mitochondrial crosstalk. This review systematically explores the intricate interactions between gut microbiota and mitochondrial function, underscoring their crosstalk as a critical mechanistic axis in obesity pathogenesis. Furthermore, it highlights the potential of TCM in developing innovative, targeted interventions, paving the way for personalized approaches in obesity treatment through the precise modulation of gut microbiota–mitochondrial interactions, offering more effective and individualized therapeutic options.